Assessing the pedestrian facilities for the blind in Kuantan city - Shaliha, Minhad; Liyana, Mohamed Yusof (Universiti Malaysia Pahang, 2019)
In highlighting sustainable urban environment, walkability becomes a key trait. The criteria that can improve walkability in urban area are the provision and ease of access of the pedestrian facilities for everyone including people with disabilities (PWDs). The mobility of PWDs in urban area are very challenging as they are facing physical, cultural and social barriers that hinder their participation in the society. Unfortunately, these difficulties are usually disregarded during the planning and implementation phases of urban development. In line with this concern, this study intends to assess the current provision and accessibility aspect of pedestrian facilities for PWDs focusing on the blind at Urban Transformation Centre (UTC), Kuantan surrounding as mean to investigate the physical obstacles that may act as potential barriers. The on-site assessment was conducted by using a checklist that was initially generated from analysing the Standards and guidelines related to pedestrian facilities and the needs of the blind in urban area. The findings reported that the pedestrian facilities for the blind in the case study area are lacking in provision and not entirely accessible specifically on alkway/sidewalk, tactile block, pedestrian crossing, handrail and ramp. The barriers underlined in the findings may act as direction for local authorities and industry to improve the pedestrian facilities for the blind and consequently, will be equally beneficial for all pedestrian.